Lessons learned what international assessments tell us about math achievement - Loveless, Tom, 1954- (Brookings Institution Press, 2007)
"Examines student performance in mathematics, using the Trends in Mathematics and Science Study database to address pressing questions about school policy and educational research, including major lessons learned from TIMSS testing, comparison of math curricula across nations, effect of technology in the classroom, and progress of popular math reforms abroad"--Provided by publisher.